Vajthó László kapcsolata a debreceni egyetemmel - Vincze, Tamás (Gerundium, 2013)
LÁSZLÓ VAJTHÓ’S LINKS WITH THE UNIVERSITY OF DEBRECEN. A literary historian known for his text editions and teacher of Dániel Berzsenyi Secondary Grammar School in Budapest, László Vajthó received habilitation for Privat-docent in 1935 at the Faculty of Arts of Debrecen’s István Tisza University and subsequently he obtained full professorship in 1944. In 1942, following the retirement of literary professor Károly Papp, it was L. Vajthó who was expected to occupy the vacant chair. However, somebody else was nominated for the position, and when the chair fell vacant again in 1945, he was repeatedly by-passed. Relying partly on Vajthó’s recollections at old age and partly on the correspondence between László Vajthó, literary historian Ferenc Zsigmond, and Margit Kis, a teacher of Nyíregyháza and a muse to both, the study highlights László Vajthó’s connection with the University of Debrecen.